2014
DOI: 10.1097/scs.0000000000000935
|View full text |Cite
|
Sign up to set email alerts
|

Ancillary Procedures Necessary for Translational Research in Experimental Craniomaxillofacial Surgery

Abstract: Introduction Swine are often regarded as having analogous facial skeletons to humans and therefore serve as an ideal animal model for translational investigation. However, there's a dearth of literature describing the pertinent ancillary procedures required for craniomaxillofacial research. With this in mind, our objective was to evaluate all necessary procedures required for peri-operative management and animal safety related to experimental craniomaxillofacial surgical procedures such as orthotopic, maxillof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…More recently, the use of the supraclavicular fasciocutaneous flap has been described for reconstructing a variety of head and neck defects, including pharyngeal, oral cavity, parotid, lateral skull base, and cutaneous defects. [1315] This flap has been shown to be well tolerated by the patient, with minimal donor-site morbidity and good viability at the recipient site. [16]…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the use of the supraclavicular fasciocutaneous flap has been described for reconstructing a variety of head and neck defects, including pharyngeal, oral cavity, parotid, lateral skull base, and cutaneous defects. [1315] This flap has been shown to be well tolerated by the patient, with minimal donor-site morbidity and good viability at the recipient site. [16]…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the similarities and differences in kinematics and kinetics between human and swine mastication can aid in better large-animal translational FJTT studies, which are warranted to improve outcomes and allow pre-clinical development of computer-assisted technologies for such surgeries (Al Rakan et al, 2014, Santiago et al, 2014). Among the similarities between swine and human mastication are both the range and profiles of condylar motion (Hannam et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified swine as having analogous facial skeletal structures and actions of mastication compared to humans. Therefore, these characteristics make swine the ideal candidate for translational investigation of FJTT (Al Rakan et al, 2014; Farkas et al, 1976; Farkas et al, 1977; Papadaki et al, 2010; Santiago et al, 2014; Strom et al, 1986). However, further understanding of swine mastication and improved opportunities for translating the swine FJTT model to humans requires reliable models of swine jaw biomechanics (Hannam 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The pre-clinical CAPE system was initially developed and tested on swine (both cadaveric and live), without incorporating human anatomy from 3D plastic models or cadavers [19,20,23]. As such, this paper addresses the translational capabilities of the CAPE system as applied to human anatomy through mock transplants performed on human plastic models and a single-human cadaver transplant.…”
Section: Introductionmentioning
confidence: 99%